The South African lady and Die Boerevrou : a comparison of the race and gender discourse within popular white women’s reading in South Africa, 1920-1929 - Sandwith, Corinne (University of Pretoria, 2025)
Thesis (PhD (English))--University of Pretoria, 2025.